The wellbeing of women in entrepreneurship : a global perspective - Lepeley, María Teresa (Human centered management (Routledge (Firm)), 2020)
Womenaccomplish nearly two-thirds of total work around the world(including household duties), comprise one-third of the formal labor force, but women receive one-tenth of the world's income and own only one-hundredth of the world's property. Entrepreneurship is a vehicle for advancing the lives of women around the world. This book brings together49distinguished entrepreneurship scholars to provide a unique global vision of the wellbeing of women entrepreneurs necessaryfor fostering sustainable development and inclusive societies. Although gender inequality isan important issue, solutions leading to gender parity are far from reaching ideal levels in the formal workplace andglobally. Meanwhile the number of women involved inentrepreneurship is growing exponentially becausethere are more opportunities for women to own a business and be their own boss. This offers women the most desirable andflexible working conditions that better align with women's lifestyles and multiple family responsibilities. However, entrepreneurial activities are demanding and complex; compared to men, women face special challenges that deserveclose attention. This book presents researchand programsto effectively support women entrepreneurs in reachinglevels of wellbeing requiredto ensure business sustainability andpersonal prosperity. Offering a diversity perspectives from around the globe, The Wellbeing of Women in Entrepreneurshipis of great interest to academics and practitioners working in teaching and research in disciplines includingbusiness management, entrepreneurship, oganizational change, humancentered management, human resources, sustainable development, and women's studies.